A review of the influence of political connections on management's decision in non-US settings. Issue 4 (27th June 2020) - Amara, Ines; Khlif, Hichem
Abstract : Purpose: Given the interest in better understanding the economic effects of political connections, this paper aims to review empirical studies in the accounting and finance domain investigating the effects of firms' political connections on management's decision in non-US settings. Design/methodology/approach: Key words used to search for relevant studies include "political connections" linked with "tax avoidance, " "earnings quality" "voluntary disclosure." The authors consult several editorial sources including Elsevier, Electronic Journals Service EBSCO, Emerald, Springer, Palgrave Macmillan, Sage, Taylor & Francis and Wiley-Blackwell. The authors' search yields 46 published studies since 2006. Findings: The review reveals a prevalence of studies conducted in Asia. A narrative synthesis of empirical findings shows mixed effects of political connections on earnings management, as measured by accrual-based or real earnings management practices. Mixed evidence also exists for the association between political connections and reporting policy (e.g. corporate social responsibility reporting). The review also reveals that firms with political ties adopt an aggressive tax policy aimed at reducing effective tax rates and are more likely to choose a Big 4 auditor. Originality/value: The review discusses the political connections literature focusing on studies outside of the USA and the effect of such connections on decision-making by management. It identifies some limitations of this literature and offers guidance for future research avenues. The synthesis suggests that political connections can adversely or beneficially impact management's decisions depending on the legal, institutional and cultural characteristics prevailing in a particular setting.